The effect of MoAlB substitutions on the oxidation behavior of ZrB2-SiC Composites at 1600 °C - Yashuang Xu; Ling Liu; Yanbo Liu; Zhuang Ma; Shirui Yang (Materials Research Express, 2024)
ZrB _2 -SiC ceramics are potential candidates for thermal protection materials for re-entry and hypersonic vehicles. Phases are typically added to ZrB _2 -SiC to enhance the oxidation resistance of the material. MoAlB is an attractive nanolaminated ternary boride compound. Due to its damage tolerance, crack healing ability, and good oxidation resistance, MoAlB is a promising material for high-temperature applications. Therefore, the effect of MoAlB substitution on the oxidation of ZrB _2 -SiC at 1600 °C for 10 h was evaluated. Five samples with different MoAlB contents (0 vol%, 4 vol%, 8 vol%, 12 vol%, 16 vol%) were prepared. The results indicate that ZrB _2 -SiC-8vol%MoAlB exhibits improved oxidation resistance compared to ZrB _2 -SiC. After being oxidized at 1600 °C for 10 h, the thickness of the oxide layer on ZrB _2 -SiC-8vol%MoAlB was significantly smaller than that on ZrB _2 -SiC. The thickness of the oxide layer in ZrB _2 -SiC was 250 μ m, while the thickness of the oxide layer in ZrB _2 -SiC-8vol%MoAlB was 108 μ m. The formation of dendritic crystals on the surface of ZrB _2 -SiC-4vol%MoAlB destroys the oxide layer, leading to a decrease in the oxidation resistance of material. The mass gain of ZrB _2 -SiC-12vol%MoAlB and ZrB _2 -SiC-16vol%MoAlB is greater, and the oxidation layer is thicker, indicating a lower oxidation resistance.